Effect of Different Offline Periods on Consolidation Process Based on Stability in Implicit Motor Memory of Veteran and Disabled Athletes - S. Ahar; M.A. Aslankhani; E. Zareian (Afarand Scholarly Publishing Institute, 2016)
Aims: In order to reach a better functioning in the athletic contests, the athletes needs to learn completely many and different motor skills. Therefore, to select properly an offline period between the motor skills are very important. The aim of this study was to investigate the effects of different offline periods on the consolidation periods based on stability in the implicit motor memory in the veteran and disabled athletes. Materials & Methods: In the practical semi-experimental study, 45 veteran and disabled athletes with physical-motor disabilities, who were members of the athletic teams of Yazd Province in order to participate in the state contests and Olympiads, were studied in Yazd City in summer 2015. The subjects were selected via available sampling method. The subjects were randomly divided into three groups including 6-, 24-, and 72-hour offline period groups. The test was conducted at two stages including learning and retention using alternating serial reaction time task (ASRTT) and serial color matching task (SCMT). Data was analyzed using two-factor ANOVA with the repeated measures, one-way ANOVA, and Duncan and Bonferroni post-hoc test. Findings: In the learning stage, the main effect of the group and the interaction effect of the group and the exercise package were not significant (p>0.05). Nevertheless, the main effect of the exercise package was significant (p=0.001). In the retention stage, the main effects of the exercise package (p=0.001) and group (p=0.048) and the interaction effect between them (p=0.001) were significant. A stability based consolidation process was seen in 24-, and 72-hour offline period groups. Nevertheless, there was a retroactive interference in 6-hour offline period group.   Conclusion: 24- and 72-hour offline periods affect the stability based consolidation process in the implicit motor memory in veteran and disabled athletes.